Phytochemicals and Antibacterial Activity of Impatiens balsamina L. Leaf Extracts Against Gram-Positive and Gram-Negative Bacteria - Fridayanthi, Putu Utari; Wijaya, Made Dharmesti; Udiyani, Desak Putu Citra; Indraningrat, Anak Agung Gede; Setiabudy, Marta (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The emergence of antibiotic resistance as one of the global public health threats makes research on new antibacterial compounds urgently needed. Among natural resources, the Impatiens balsamina plant has the potential to be explored as the new source of antibacterial agents. This study aimed to identify the phytochemical composition and evaluate the antibacterial activity of I. balsamina leaf extracts against Gram-positive and Gram-negative bacteria. Extracts were prepared using the maceration method with methanol, chloroform, and n-hexane solvents at a 1:5 sample-to-solvent ratio. Phytochemical screening was performed qualitatively, and antibacterial activity was evaluated using the disc diffusion assay. Analysis of methanol extract detected the presence of flavonoids, saponins, tannins, phenols, steroids, and glycosides, while chloroform extract consisted of tannins, phenols, and steroids. On the other hand, steroids were the only compounds detected qualitatively in n-hexane extract. Antibacterial testing revealed that methanol extract exhibited the highest activity, with zones of inhibition (ZOI) of 15.10±0.18 mm, 9.40±0.30 mm, 14.75±1.28 mm, and 8.67±0.50 mm against Streptococcus mutans FNCC 0405, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603, respectively. A concentration-dependent ZOI was observed in the methanol extract, with activity increasing at higher concentrations. GC-MS analysis of the methanol extract identified 32 compounds, including n-hexadecanoic acid (12.12%), 2-acetylbenzoic acid (8.26%), 5-hydroxymethylfurfural (8.21%), and 2-methoxy-4-vinylphenol (4.67%), which are known to possess antimicrobial, antioxidant, and anti-inflammatory activities. Chloroform extract showed moderate activity against S. mutans (7.04±0.15 mm) and S. aureus (7.10±0.31 mm), while n-hexane extract exhibited no antibacterial activity. The significant antibacterial activity of methanol extract is likely due to its rich phytochemical composition, highlighting methanol as an effective solvent for extracting bioactive compounds. These findings provide a strong foundation for further exploration of I. balsamina leaf extracts as a source of antibacterial agents.